c-Axis Fabric of the South Pole Ice Core, SPC14 - Voigt, Donald E. (IEDA: US Antarctic Program Data Center, 2017)
Thin sections of the South Pole Ice Core, SPC14, were prepared from samples taken every ~20 meters starting at 100 meters depth. Samples from 140 meters to 1739 meters depth were analyzed to determine the c-axis fabric of the grains. The ice is generally fine-grained, with the samples at 100 and 120 meters depth too fine grained for successful analysis, but sufficient grain growth having occurred for analysis of all deeper samples. The c-axis fabric was measured on the automated c-axis fabric analyzer located at Penn State University, designed and built by Larry Wilen. Raw data is in the form of multiple images of the ice thin section taken at defined angles under cross polarized light. The images are analyzed to determine position of the extinction minimum of each grain within the thin section, this being the orientation of the c-axis of that grain. During processing, the area of each analyzed grain is also measured. Shallow samples show a fairly random distribution, although with a slight tendency for clustering of c-axes toward the vertical. With increasing depth, the c-axes rotate toward a vertical plane with a slight additional tendency of clustering toward the vertical within that plane. The core was not oriented during collection, so it is not possible to unambiguously tell how the vertical plane is related to ice flow, but physical understanding indicates that it is transverse to flow.